Evaluation of Two Types of Intramedullary Jones Fracture Fixation in a Cyclic and Ultimate Load Model. Issue 4 (27th November 2019) - Willegger, Madeleine; Benca, Emir; Hirtler, Lena; Kasparek, Maximilian F.; Bauer, Gregor; Zandieh, Shahin; Windhager, Reinhard; Schuh, Reinhard
ABSTRACT: Implant choice is a matter of concern in athletes and active patients who sustain a Jones fracture because they are prone to failure including non‐union, screw failure, and refracture. The aim of this study was to compare the biomechanical behavior of a Jones fracture‐specific screw (JFXS) with a cannulated headless compression screw (HCS) in a simulated partial weight‐bearing and ultimate load Jones fracture fixation model. Ten matched pairs of human anatomical specimens underwent Jones fracture creation and consecutive intramedullary stabilization with a solid JFXS or a cannulated HCS. The bone mineral density was assessed prior to testing. Cyclic plantar to dorsal loading was applied for 1000 cycles, followed by load to failure testing. Angulation was measured by an opto‐electronic motion capture system and mode of failure classification was determined by video analysis. Paired analysis showed no statistically significant difference between both screw constructs. Ultimate load reached 236.9 ± 107.8 N in the JFXS group compared with 210.8 ± 150.7 N in the HCS group ( p  = 0.429). The bone mineral density correlated positive with the pooled ultimate load ( R  = 0.580, p  = 0.007) for all constructs and negatively with angulation ( R  = −0.680, p  = 0.002) throughout cyclic loading. Solid fracture‐specific and cannulated headless compression screws provide equal ultimate loads and stiffness for Jones fracture fixation. A low bone mineral density significantly impairs the construct stability and the ultimate load of both intramedullary screw constructs. © 2019 The Authors. Journal of Orthopaedic Research ® published by Wiley Periodicals, Inc. on behalf of Orthopaedic Research Society J Orthop Res 38:911‐917, 2020